BATASAN PEMILIKAN TANAH SECARA ABSENTEE/GUNTAI - Surya Senimurtikawati, Ni Wayan; Gatrawan, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Indonesia had regulated its basic regulation regarding land management asstipulated within Act No. 5 Year 1960 (UUPA). Due to that, a problem had arisenregarding the ownership of absentee land which had been restricted and certain exceptionstoward the provisions. Method that used in this research is the normative research method.Principles existed within UUPA had obliged agricultural land to actively utilized in orderto prevent the practice of exploitation. It remarks the restriction of absentee landownership along with certain expectation as stipulated in Article 10 UUPA and furtherregulated through Government Regulation No. 224 Year 1961 (has amended byGovernment Regulation No. 41 Year 1964). The exceptions also set out in the variouslegislations.
Keywords: land ownership, absentee, guntai